Baltijos valstybių klausimas Vakarų valstybių politikoje 1943 metais - Kraujelis, Ramojus (Lietuvos istorijos studijos, 2003)
The fate of the Lithuania and other Baltic States was determined during the years of World War II. The most important, still unanswered question in Lithuanian historiography is when exactly the fate of Baltic States was doomed.The main role in the considerations of the fate of the Baltic States was played by three Great Powers. The United States of America and Great Britain were those Western powers that represented the point of view of Western democracy on the issue of the occupation and annexation of Lithuania and other Baltic states.The year 1943 brought changes not only in the military fronts but also to international relations. On the eve of Soviet military victories in the East, the Soviet Union shifted the focus of foreign policy to postwar domination in Europe. That had an impact on the changes of attitudes of the Great Western States toward the problem of the Baltic States. The first main decisions on the future of the postwar Europe were made in the Big Three conference in Tehran. Though the question of Baltic States was not included in the agenda of this conference, discussion points had affected the issue of the Baltic states. Because the Western Allies hoped that Stalin would continue the cooperation with the Western powers, USA and Britain accepted Stalin's demands for security in Tehran. Baltic states in inter-Allied relations were used as a bargaining chip. Realizing that, U.S. president Roosevelt in the conversation with Stalin declared that he would not go to war with the Soviet Union after it re-occupied these lands. Stalin refused further to discuss the question of Baltic States. Incoherent, passive policy of the two great Western states toward the issue of the Baltic States in Tehran determined that Baltic States were turned to the Soviet security interest sphere.Western states remained firm in their legal commitment that final settlement of frontier questions would be resolved only at the Peace Conference. The legal non-recognition of the Baltic forcible annexation did survive the trying times of World War II, but the question of Baltic states was eliminated from the agenda of political considerations of other Big Three conferences.